Pengaruh Kemandirian dan Motivasi terhadap Hasil Belajar Siswa Daring Bahasa Jawa di Sekolah Dasar - Megandari Surgana (Jurnal Kualita Pendidikan, 2023)
Students at the Public Elementary School in Cluster Bawana Ageng, Tembalang District, showed a significant decrease in their learning outcomes for Javanese after implementing online learning. This is due to the lack of student learning independence which can be seen from the dependence of students on parents while studying at home. This type of quantitative research. The population is all students of Gugus Bawana Ageng Tembalang Public Elementary School, Semarang. The sample is 179 based on calculations using the Slovin formula. The instrument is a questionnaire. Data analysis through instrument test, prerequisite test and linear regression test. The results of this study indicate that independent learning affects students' language learning outcomes (t-count 8.257 > t-table 1.97353 and sig 0.000 <0.05) with a large effect of 37.9%. Learning motivation has an effect on students' learning outcomes in Javanese (t-count 11,011 > t-table 1.97353 and sig value 0.000 <0.05) with a large influence of 49.4%. Learning independence and learning motivation simultaneously affect students' learning outcomes in Javanese (F-count of 6.525 > F-table of 3.05 and Sig value of 0.00 <0.05) with a large influence of 62.6%.